Studi Eksegesis 1 Korintus 2:14-3:1 Sebagai Kajian Psikobiblika Dalam Memahami Perilaku Umat Kristen - Juanda, Juanda; Karina, Nina Astrid (Jurnal Teologi dan Pelayanan Kerusso, 2024)
Interpretations regarding the meanings of the phrases "spiritual man" and "natural man" as found in the text 1 Corinthians 2:14-3:1 have led to differences of opinion among scholars and theologians. There are at least three concepts related to the terms "spiritual man" and "natural man". First, these entities refer to the core of human nature which possesses contrasting characteristics. Second, there is a gradual development of the spiritual dimension within a person. Third, the inner state of humans is also characterized by the alternating dominance between spiritual and worldly aspects. The possible causes of variations in interpretations related to the terminology of "spiritual man" and "natural man" may be due to differences in the usage of different original texts, especially "natural man" which uses ψυχικὸς ἄνθρωπος in chapter 2 and σαρκίνοις in chapter 3. Differences in textual sources indicate variations in contexts and usage, which can lead to diverse understandings of these terms. Research conducted using Grassmick's nine-step qualitative exegesis method aims to seek the meanings of the phrases "spiritual man" and "natural man". From a series of exegetical processes that have been carried out, the analysis results show that the concept of "natural man" (ψυχικὸς ἄνθρωπος and σαρκίνοις) has fundamental differences with the "spiritual man" (ὁ πνευματικὸς), as these terms not only refer to sequential or interchangeable spiritual conditions, but also describe a fundamental status in someone's regeneration in Christ.